Deciphering a cryptic minefield: A guide to Cryptosporidium gp60 subtyping - Robinson, Guy; Chalmers, Rachel M.; Elwin, Kristin; Guy, Rebecca A.; Bessonov, Kyrylo; Troell, Karin; Xiao, Lihua (Current research in parasitology & vector-borne diseases, 2025)
For 25 years, analysis of the gp60 gene has been the cornerstone of Cryptosporidium subtyping, particularly for Cryptosporidium hominis and Cryptosporidium parvum, during population-based and epidemiological studies. This gene, which encodes a 60 kDa glycoprotein, is highly polymorphic with several variable features that make it particularly useful for differentiating within Cryptosporidium species. However, while this variability has proven useful for subtyping, it has on occasion resulted in alternative interpretations, and descriptions of novel and unusual features have been added to the nomenclature system, resulting in inconsistency and confusion. The components of the gp60 gene sequence used in the nomenclature that are discussed here include “R” repeats, “r” repeats, alphabetical suffixes, “variant” designations, and the use of the Greek alphabet as a family designation. As the subtyping scheme has expanded over the years, its application to different Cryptosporidium species has also made the scheme more complex. For example, key features may be absent, such as the typical TCA/TCG/TCT serine microsatellite that forms a major part of the nomenclature in C. hominis and C. parvum. As is to be expected in such a variable gene, different primer sets have been developed for the amplification of the gp60 in various species and these have been collated. Here we bring together all the current components of gp60, including a guide to the nomenclature in various species, software to assist in analysing sequences, and links to useful reference resources with an aim to promote standardisation of this subtyping tool. [Display omitted] •Provision of recommended, standardised rules for gp60 nomenclature.•Description of features underlying the nomenclature in different Cryptosporidium spp.•Pitfalls and historical alternative interpretations are highlighted.•Resources to assist the community in gp60 subtyping.